2012
DOI: 10.1016/j.jglr.2012.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Is the fishery of the introduced Tanganyika sardine (Limnothrissa miodon) in Lake Kivu (East Africa) sustainable?

Abstract: Limnothrissa miodon, a small pelagic clupeid fish introduced at the end of the 1950s into Lake Kivu, became an important resource for the human populations of this area. The total stock of pelagic fish populations of this lake was estimated in 2008 by two hydroacoustic surveys, using an EK60 split-beam sounder (frequency 70 kHz). The total fish stocks were estimated to be approximately 5000 t in the rainy season and 6000 tons in the dry season. These values are similar to previous estimations performed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 44 publications
2
26
0
1
Order By: Relevance
“…Several acoustic studies have shown that if night-time datasets are different from daytime datasets [38,39], there is a positive significant correlation between the acoustic densities obtained for the two periods [40]. Thus, even if night-time data may be more accurate (the fish is usually scattered, that allows the extraction of a higher number of individual targets, and provides a more homogeneous distribution of the fish), the analysis of daytime data can be accepted as it has been done in other aquatic ecosystems [27,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several acoustic studies have shown that if night-time datasets are different from daytime datasets [38,39], there is a positive significant correlation between the acoustic densities obtained for the two periods [40]. Thus, even if night-time data may be more accurate (the fish is usually scattered, that allows the extraction of a higher number of individual targets, and provides a more homogeneous distribution of the fish), the analysis of daytime data can be accepted as it has been done in other aquatic ecosystems [27,41].…”
Section: Discussionmentioning
confidence: 99%
“…Hydro-acoustic data were collected using a standardised protocol of mobile vertical echo sounding used in similar ecosystems [26,27] including calibration steps as described by Foote et al [28]. Prospecting has been performed along zig-zag tracks going downstream, at high tide, at a mean speed of 5 km/h-1, only during daytime for security reasons.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Beyond Europe and North America, another well-studied area is the African Rift Valley and Great Lakes, including Victoria, Malawi and Kivu. The sustainability of Lake Kivu's fishery for the introduced Tanganyika sardine (Limnothrissa miodon) has been assessed (Guillard et al 2012), and the diet and feeding behavior of pelagic fish studied using a combination of stomach content analysis and hydroacoustic surveys in Lake Malawi (Allison et al 2008). Lake Victoria has been the focus of considerable hydroacoustic survey effort in recent years -likely the result of the introduced Nile perch (Lates niloticus) and declining cichlid populations (e.g.…”
Section: Africamentioning
confidence: 99%
“…Authors have integrated several variables acting on the relation between TS and fish length to increase the accuracy of estimates, such as the fish orientation in the beam (Kubecka and Duncan 1998;Lilja et al 2000;Frouzova et al 2005). Thus, hydroacoustics can describe the structure of a population; size distribution, cohort organization and distribution in the water column can be consequently observed at small spatial scales (Brehmer et al 2003;Bertrand et al 2010;Guillard et al 2012a). …”
Section: Advantagesmentioning
confidence: 99%
“…Echo-integration, which integrates the return-echo strength in the echosounder's sampled volume, is used to estimate the number of fish in the detection beam (Simmonds and MacLennan 2005). This method has been used efficiently in numerous studies of marine fish populations (Josse et al 1999;Brehmer et al 2006b;Doray et al 2010) or lake fish population monitoring (Guillard et al 2006;Winfield et al 2009;Mehner et al 2010;Guillard et al 2012a), among numerous references. Furthermore, echo properties provide descriptive information about the targets themselves.…”
Section: Advantagesmentioning
confidence: 99%